Analysis of the Potential of Regional Taxes and Levies in Increasing Regional Original Income in South Buru Regency - Muamar F. Marasabessy; Amaluddin; Jeanee B. Nikijuluw (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Locally Generated Revenue (PAD) is a crucial indicator for assessing a region's level of fiscal independence, particularly in the era of fiscal decentralization. As a newly autonomous region, South Buru Regency still faces the challenge of low contributions of local taxes and levies to total PAD, resulting in a relatively high dependence on central government transfers. This situation demands a comprehensive empirical analysis to identify the potential of local taxes and levies to sustainably increase PAD. This study aims to analyze the influence of regional tax capacity on local revenue (PAD) in South Buru Regency by considering the role of other economic and fiscal factors, namely Gross Regional Domestic Product (GRDP), capital expenditure, and General Allocation Fund (DAU). The analytical method used is a time series econometric approach using the Error Correction Model (ECM), which begins with a stationarity test, the Johansen cointegration test, and estimation of short-term and long-term relationships. The data used is secondary data for the period 2015–2024. The results show that all variables are integrated at the same order and exhibit a cointegration relationship, indicating a long-term equilibrium between PAD and its explanatory variables. In the short term, tax capacity and capital expenditure have a positive and significant effect on PAD, while GRDP and DAU have not shown a significant influence. In the long term, tax capacity remains the main determinant of PAD growth, while DAU tends to have a negative impact on regional fiscal independence. These findings confirm that optimizing the potential of regional taxes and levies is a key strategy in strengthening PAD in South Buru Regency.